Self Tuning Sliding Mode Control for Quadrotor Waypoint Tracking - Istiqphara, Swadexi; Agustinah, Trihastuti; Fatoni, Ali (IPTEK Journal of Proceedings Series, 2015)
In this paper, self-tuning sliding mode control is proposed to control quadrotor with mass parameter uncertainty on waypoint trajectory tracking. Parameter uncertainty is one of the factor that cause instability of quadrotor. Self-tuning sliding mode control is used to maintain the stability of quadrotor in this parametric uncertainties condition. The simulation results show that the quadrotor can track the waypoint trajectory in the presence of parameter uncertainty.